Has COVID-19 improved public awareness on oral hygiene? - Sorooshian, Shahryar; Kumar, Senthil (Tehran University of Medical Sciences (TUMS), 2021)
Since the onslaught of COVID-19 started in China at the end of 2019, many governments across the world have actively propagated the importance of hand hygiene, and social distanc-ing. Although Sampson, has highlighted that COVID-19 complications are related to high bac-terial load in the mouth, not many media have promoted the role of oral hygiene in controlling of COVID-19 (1)